The Bureaucratic disconnect in collaborative institutions: A Case of Rural Water Supply in Punjab, Pakistan - Waheed, Seemi; Sial, Maqbool; Azhar, Aisha (International Journal of Water Governance, 2023)
The collaborative model for rural water supply (RWS), introduced at the behest of international funders in the 1990s, experienced only partial success owing to the low accept- ability of public managers and the slow process of community development (CD). This article goes into the empirical findings of a study that is based on in-depth interviews with 20 staff and line public managers of the four RWS in different regions as well as on content analysis of policy documents and funding organizations’ reports. The results indicate that appropriate CD, reforms in internal organization arrangements, and understanding of context-specific social, economic, and political diversity remain necessary in collaborative compliance with institutions for RWS sustainability. The study aims at making a contribution to the theory of collaborative governance and the practice of collaborative implementation in developing countries.